Chapter 9 Reading Galen in Byzantium The fate of Therapeutics to Glaucon - Bouras-Vallianatos, Petros (Taylor & Francis, 2018)
In this chapter, I shall focus on the Galenic corpus, whose dissemination in the Byzantine world was widespread and influential; in particular, I have chosen to examine the various revivals of Galen's Therapeutics to Glaucon, which was copied widely. A number of authors produced commentaries based on this treatise and some were invariably influenced by it in composing their own works throughout the Byzantine era (AD 330-1453).4 My study is not exhaustive, but rather I shall select specific examples of interest from the various forms of evidence. First, I shall provide some basic introductory details on Galen's Therapeutics to Glaucon, followed by a section on its circulation and textual transmission in Byzantium. Then, I shall go on to discuss its revival by Byzantine medical authors into two further sections; the first focuses on commentaries and the second deals with medical handbooks.